Planktonic Foraminiferal Biostratigraphy of the Upper Cretaceous of the Central European Basin - Danuta Peryt; Zofia Dubicka; Weronika Wierny (Geosciences, 2022)
Planktonic foraminifera are one of the most stratigraphically important groups of organisms for the Cretaceous system. However, standard foraminiferal zonations based mostly on species from the Tethyan bioprovince are hardly applicable in temperate regions where warm-water taxa are scarce or lacking. We propose a foraminiferal zonation based on foraminiferal events recognized in the northern Foraminiferal Transitional Bioprovince, which likely has a high correlation potential at least at a regional scale. Fifteen planktonic foraminiferal zones are distinguished from the upper Albian up to the uppermost Maastrichtian strata in extra-Carpathian Poland and western Ukraine. From the bottom to the top, Thalmanninella appenninica, Th. globotruncanoides, Th. reicheli, Rotalipora cushmani, Whiteinella archaeocretacea, Helvetoglobotruncana helvetica, Marginotruncana coronata, M. sinuosa, Pseudotextularia nuttalli, Globotruncana linneiana, G. arca, Contusotruncana plummerae, Rugoglobigerina pennyi, Globotruncanella petaloidea and Guembelitria cretacea. These zones are calibrated by macrofaunal zonations.